Augmented Reality (AR) Generated Value-in-Use Experiences: Literature Review and Analysis - Adel, Riham (The Arab Journal of Administration, 2024)
Augmented Reality (AR) research has sparked both academia and practice interest. However, despite the increasing interest to study this emergent topic, till now the growing body of knowledge is mainly from engineering and computer science disciplines. The aim of this study is to conduct a systematic literature review to identify, evaluate and synthesize (AR) emergent themes from business management publications in the last years. Hence, contribute to the literature with evidence-based results about the existing research progress, and classify into clusters with multidimensional interrelationships to help researchers build up on these findings and expand (AR) research from business standpoint. The study is exploratory and qualitative in nature; a structured hybrid- narrative review method is used to extract unstructured data within articles. Thus, discover relevant patterns, uncover hidden thematic clusters, relationships, and identify multidimensionality of dominant concepts from the existing (AR) business literature. It was evident from the stream of research, that most of researchers’ have a clear interest in exploring the interactive nature of Augmented Reality (AR) as new digital technology and defining its experiential characteristics with a hierarchical set of dimensions that will affect customers’ perceptions of service operations. Hence, in line with these findings, and grounded on the service literature body of knowledge, Augmented Reality can be defined as: “smart service